IDENTIFIKASI FAKTOR RISIKO TERJADINYA KOLONISASI SPESIES CANDIDA DI RONGGA MULUT PADA INDIVIDU SEHAT (PENELITIAN PADA MAHASISWA & MAHASISWI FKG UI) - Audiawati Audiawati; Siti Aliyah Pradono; Febrina Rahmayanti (Lembaga Penelitian Universitas YARSI, 2015)
Introduction : Cases of oral candidiasis are commonly found, both in healthy individuals and immunecompromise patients, however publications of Candida carrier in the oral cavity of healthy population and risk factors for colonization in Indonesia are hardly available. Objective : This study was aimed to analyze the type and number of Candida colonies and identify risk factors in the oral cavity of apparenthly health FKG UI students. Material and methods : the specimens were taken from 195 subjects with oral rinse technique for identification using culture medium CHROMagar® and Sabaraoud dextrose agar. Results and discussion : Candida species were found in the 107 subjects oral cavity (54.87%), being Candida albicans was is the predominant species (52.33%). Some 88 subjects (82.24%) was dominant in the number of colonies less than 400 CFU/ml, while the rest had colony of more than 400 CFU/ml (17.76%). Candida colony grew dominantly in single colony (90.65%), and the others showed multi-species colonies (9.34%). Risk factors identified included age; gender; hormonal; blood type O; denture; orthodontic appliances; unstimulated salivary flow; pH of saliva; smoking, alcohol and oral cleaning habit; and oral health status. By using a statistical Pearson chi-square test, no significant relationship was found between risk factors and number of Candida colonies in the oral cavity p less than 0.05. Conclusion : there was no one single risk factor for Candida colonization, but combination of various risk factors for demographis, local and systemic was observed